Calculation of Organizational-Technological Tasks by Ensuring the Stability and Reliability; Erection of Multi-Storey Frame Buildings - M.A, Salahov; ., . (International Journal of Engineering and Technology, 2018)
In the article fundamentally new problems are considered - the calculation of organizational and technological tasks by ensuring the stability of multi-storey frame buildings. Multi-storey frame construction is a very complex spatial rod systems with inclusion of planar and volumetric elements from prefabricated and monolithic reinforced concrete or metal lattice systems in them and is used in almost all fields of the national economy.Â